2005
DOI: 10.1177/1359105305053422
|View full text |Cite
|
Sign up to set email alerts
|

The Social Realities of Adherence to Protease Inhibitor Regimens: Substance Use, Health Care and Psychological States

Abstract: Adherence to HIV antiretroviral treatments is impacted by a variety of factors nested within the realities of people's lives. To understand this phenomenon, we undertook an investigation to assess HIV medication adherence in a community-based sample of 300 HIV seropositive men-who-have-sex-with-men (MSM). Using multiple measurement strategies (self-report, electronic monitoring, calendar-based assessments) we assessed factors related to medication adherence. Our findings indicate that adherence to protease inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 63 publications
(73 reference statements)
3
52
0
Order By: Relevance
“…That stimulant use, including cocaine, may adversely impact medication adherence is generally consistent with the extant literature (e.g., Arnsten et al, 2002;Halkitis, Kutnick, & Slater, 2005;Ingersoll, 2004;Sharpe, Lee, Nakashima, Elam-Evans, & Fleming, 2004). Some have suggested that disruptions to sleep and eating patterns and the increased level of environmental instability attendant to stimulant abuse may drive lower adherence rates (Reback, Larkins, & Shoptaw, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…That stimulant use, including cocaine, may adversely impact medication adherence is generally consistent with the extant literature (e.g., Arnsten et al, 2002;Halkitis, Kutnick, & Slater, 2005;Ingersoll, 2004;Sharpe, Lee, Nakashima, Elam-Evans, & Fleming, 2004). Some have suggested that disruptions to sleep and eating patterns and the increased level of environmental instability attendant to stimulant abuse may drive lower adherence rates (Reback, Larkins, & Shoptaw, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…This four-group method of classification was used in other studies to classify HIV medication adherence (Carrieri et al, 2001;Hill et al, 2003;Mannheimer, Friedland, Matts, Child, & Chesney, 2002). As noted in previous analyses (Halkitis et al, 2005), the methods yield significantly equivalent results. Thus, in the ensuing analyses we utilize only the adjusted EDM data to examine the relations of interest.…”
Section: Treatment and Adherence Characteristicsmentioning
confidence: 83%
“…Our analysis did not take into account any objective measures used to assess depressive symptoms of participants. In addition, while a relation between drug use and sub-optimal adherence to medication has been established (Halkitis et al, 2005), it is not known whether lack of adherence stems from impaired cognitive functioning due to substance use (Rosselli & Ardila, 1996), the type of lifestyle led by someone using illicit substances (Hinkin et al, 2004), or some combination of both. Future analyses of the data should account for these behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolating independent contributions of methamphetamine use and homelessness on HIV disease progression in HIV-infected groups with significant economic and healthcare disparities is an important future research direction. Methamphetamine abuse has been identified as a negative predictor of antiretroviral adherence (Halkitis et al 2005;Moss et al 2004;Reback et al 2003) and there are some suggestions that it may have direct immunological effects that could associate with poor biological outcomes (Gavrilin et al 2002;Markowitz et al 2005).…”
Section: Discussionmentioning
confidence: 99%